Serum Hepcidin Level as a Marker of Iron Status in Children with Cystic Fibrosis - Monika Kałużna-Czyż; Urszula Grzybowska-Chlebowczyk; Halina Woś; Sabina Więcek (Mediators of Inflammation)
Introduction. Iron deficiency is common in patients with cystic fibrosis. Conventional iron status markers are often abnormal in patients with CF, reflecting inflammation and/or infection, rather than actual iron stores. The aim was to evaluate serum hepcidin levels against selected iron status markers, assuming that hepcidin may be a more sensitive indicator of iron management in patients with active inflammation, such as those with CF. Material and Methods. 46 children with cystic fibrosis and 31 healthy controls were enrolled. Hepcidin concentration was evaluated, along with the following other blood assays: full blood count, Fe, ferritin, transferrin, TIBC, liver markers, and CRP. Results. Higher ferritin and CRP levels as well as lower TIBC levels significantly predicted hepcidin levels in the study group, control group, and the entire sample. There was no significant difference in hepcidin levels between the patients and controls. Children with exacerbations had significantly higher hepcidin levels than those with stable disease. These findings support the serum hepcidin level as useful in assessing iron status in children with cystic fibrosis. It may also be useful in early detection and monitoring of treatment of exacerbations.